Successful management of heart failure 45 years after surgical correction of tetralogy of Fallot. Issue 2 (February 2021) - Otsuka, Kaishi; Kawano, Hiroaki; Ishimatsu, Takashi; Yoshimuta, Tsuyoshi; Doi, Yoshiyuki; Fukae, Satoki; Koga, Seiji; Ikeda, Satoshi; Eishi, Kiyoyuki; Maemura, Koji
Abstract: A 59-year-old Japanese woman was admitted with heart failure due to severe pulmonary regurgitation and tricuspid regurgitation, in addition to atrial fibrillation 45 years after surgical correction of tetralogy of Fallot (TOF). She had been under treatment with medication and catheter ablation for arrhythmia including ventricular tachycardia for the past 28 years. She underwent pulmonary valve replacement as well as tricuspid and mitral valvuloplasty, which obviously improved her status even though her right ventricular end-diastolic volume index exceeded the recommended threshold. Patients who have undergone surgical correction of TOF need to be managed over the long term. <Learning objective: For a long term after surgical correction of tetralogy of Fallot (TOF), appropriate managements are needed for arrhythmia and heart failure related to heart valve disease. Even though her right ventricular end-diastolic volume index exceeded the recommended threshold by the current published guidelines, re-operation for heart valve diseases improved the present patient. We have to accumulate evidence to make useful guideline of re-operation of TOF in Japan.>